2013
DOI: 10.1111/vde.12082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and cyclo‐oxygenase‐2 expression in five dogs with solar dermatitis/actinic keratosis treated with firocoxib

Abstract: A role for COX-2 might thus be hypothesized in the pathogenesis of canine solar dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…In one study, 87.5% (7/8) of dogs with cutaneous SCC were found to have positivity for cyclo‐oxygenase‐2 (COX‐2) expression and 100% (9/9) in another study . Additionally, COX‐2 expression has also been identified in canine cases of actinic keratosis, and therapy with NSAIDs provided improvement in 4/5 dogs . NSAIDs have also been used in people with actinic keratosis with some efficacy as a topical therapy .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, 87.5% (7/8) of dogs with cutaneous SCC were found to have positivity for cyclo‐oxygenase‐2 (COX‐2) expression and 100% (9/9) in another study . Additionally, COX‐2 expression has also been identified in canine cases of actinic keratosis, and therapy with NSAIDs provided improvement in 4/5 dogs . NSAIDs have also been used in people with actinic keratosis with some efficacy as a topical therapy .…”
Section: Discussionmentioning
confidence: 99%
“…56,57 Additionally, COX-2 expression has also been identified in canine cases of actinic keratosis, and therapy with NSAIDs provided improvement in 4/5 dogs. 32,56,57 NSAIDs have also been used in people with actinic keratosis with some efficacy as a topical therapy. 58 Although it is difficult to draw conclusions from NSAID usage in this study, there is the impetus for future studies investigating the role of NSAIDs as chemoprevention for solar UV-radiation associated SCC in dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In veterinary medicine, firocoxib is largely used for the management of osteoarthritis or surgical pain . Recently, it has been successfully tested in dogs with solar dermatitis and hyperplastic/dysplastic epithelial lesions of potential preneoplastic significance . Furthermore, a study demonstrated the antitumor activity of firocoxib as single agent or in association with cisplatin in dogs with transitional cell carcinoma …”
Section: Introductionmentioning
confidence: 99%